Strategic investment in international gas-transport systems: a dynamic analysis of the hold-up problem - Franz Hubert; Irina Suleymanova (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
We develop a dynamic model of strategic investment in a transnational pipeline system. In the absence of international contract enforcement, countries may distort investment in order to increase their bargaining power, resulting in overinvestment in expensive and underinvestment in cheap pipelines. With repeated interaction, however, there is a potential to increase efficiency through dynamic collusion. In the theoretical part we establish a fundamental asymmetry: it is easier to avoid overinvestment than underinvestment. Calibrating the model to fit the Eurasian pipeline system for natural gas, we find that the potential to improve efficiency through dynamic cooperation is large. In reality, however, only modest improvements over the non-cooperative solution have been achieved.
Keywords: L95; L14; C71; 330; Multilateral bargaining; hold-up; irreversible investment; collusion; Gasleitungstransport; Investition; Verhandlungen; Sunk Costs; Wettbewerbsbeschränkung; Welt; Europa; Russland; Asien